Unilateral interstitial lung disease: A unique manifestation of asymptomatic pulmonary artery atresia (Indian Journal of Case Reports, 2024)
Interstitial pulmonary fibrosis is idiopathic, bilateral, or secondary to exposure to organic antigens, or collagen disorders. Unilateral pulmonary fibrosis is uncommon and intriguing as it has different pathogenetic mechanisms. We present a case of a patient with a short 5-day history of dyspnea with no ailment in childhood. His radiograph revealed increased reticular markings in the right lung with a small right hilum. Contrast-enhanced computed tomography showed unilateral pulmonary fibrosis and confirmed the presence of an atretic right pulmonary artery contributing to the small hilum, with collateral supply from the right internal mammary artery. This asymptomatic patient had unilateral pulmonary fibrosis which had developed as a consequence of impaired blood supply to the right lung due to atresia of the right pulmonary artery with collateral from systemic circulation unable to keep abreast with normal pulmonary development.